Effect of freeze–thaw cycles on the void topologies and mechanical properties of asphalt. (15th August 2022) - Sanfilippo, D.; Garcia-Hernández, A.; Alexiadis, A.; Ghiassi, B.
Highlights: Asphalts with three air voids contents were manufactured. These were subjected to freeze–thaw cycles. The mechanical properties of asphalts and their void shapes were correlated. Water retention in the pores is key to determine the durability of asphalt. Abstract: Frost and thawing damage asphalt in cold climates. Water that enters the pores of asphalt at low temperatures may accelerate its degradation. Water can expand into pores, altering the void content and shape, thus affecting the asphalt's internal structure and fracture properties. We can develop more durable asphalt types if we understand how void topology changes with freeze–thaw cycles. The purpose of this study is to establish a correlation between the mechanical properties of asphalts and the topological properties of voids. To determine their internal structure, various asphalt types representing dense asphalt and asphalt with voids were made and X-rayed before and after each freeze–thaw cycle. We also obtained the mechanical properties of asphalt and correlated them with the void properties. It was found that dense asphalt has the lowest degradation rate in wet conditions characterised by non-connected gaps, which was approximately constant with freeze–thaw cycles; however, dense asphalt was least durable under dry conditions compared with asphalts with more voids. Due to its high water retention rate, asphalt with a 10% void content degraded at an accelerated rate during the initial cycles. As a result of bigger voids, asphalt with a higher pore content plateaued in later cycles due to reduced water retention. This study demonstrates that the internal void topology affects the mechanical properties of asphalt during freeze–thaw cycles. These results can be used to understand changes in asphalt mechanical losses resulting from freeze-thaw cycles and to validate numerical models to perform parametric studies of the asphalt's freeze–thaw degradation.